2017
DOI: 10.4025/actascitechnol.v39i4.30198
|View full text |Cite
|
Sign up to set email alerts
|

<b>Sugarcane bagasse pellets: characterization and comparative analysis

Abstract: ABSTRACT. This paper presents a study carried out in a Brazilian pellet industry in order to determine the main properties of sugarcane bagasse pellets. Materials ), ash content (8.70%), fixed carbon (14.03%), volatile matter (77.27%), nitrogen (0.28%), sulphur (0.02%) and chlorine (< 0.02 %). The results are compared with those obtained from the literature and discussed according to international standards for biomass pellets, wood pellets and solid biofuel. The comparative analysis showed that there are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…Therefore, both the composite and pure pellets technically would fall in the strictest classes, as their water contents were in compliance with the requirements of international standards for this property. Almeida et al [ 21 ] documented 77.25% volatile matter, 14.05% fixed carbon, and 8.70% for pellets from sugarcane bagasse, consistent with the proximal composition of pellets in this study, regardless of the type, whether composite and pure. The ISO 17225-2 and 17225-6 set the ash content to be no greater than 0.7 and 6% for the residential and commercial classes, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, both the composite and pure pellets technically would fall in the strictest classes, as their water contents were in compliance with the requirements of international standards for this property. Almeida et al [ 21 ] documented 77.25% volatile matter, 14.05% fixed carbon, and 8.70% for pellets from sugarcane bagasse, consistent with the proximal composition of pellets in this study, regardless of the type, whether composite and pure. The ISO 17225-2 and 17225-6 set the ash content to be no greater than 0.7 and 6% for the residential and commercial classes, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Globally, supportive material of residual biomass from distillation of cellulosic ethanol enabled the hybrid non-wood pellets to be technically comparable and even superior to those from processing sugarcane bagasse [ 21 ], wheat straw [ 23 ], Moso bamboo [ 24 ], sewage sludge plus Chinese fir, Camphor and rice straw [ 6 ], residues of olive tree [ 25 ] and corncob [ 26 ], and other woody and non-woody wastes regular in the production of pellets on an industrial scale ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…External fraction is structurally less affected by the pretreatment, [3] and it is a denser material and it can be aggregated/pelletized with more efficiency than sugarcane bagasse. [30][31][32] A study with a mixture biomass revealed that the smallest particle size evaluated (0.08 mm) resulted in 95.7 % of glucose yield, compared to the largest separation sizes, 2 and 6 mm, 78.4 and 74.6 %, respectively. [6] For milling biomass showed that the smallest particle evaluated (3 mm) increased digestibility by 80 %, while a larger particle (10 mm) showed lower digestibility (60 %).…”
Section: Discussionmentioning
confidence: 99%
“…One characteristic that can influence the enzyme action on the material is the density. External fraction is structurally less affected by the pretreatment, and it is a denser material and it can be aggregated/pelletized with more efficiency than sugarcane bagasse …”
Section: Discussionmentioning
confidence: 99%
“…Globally, addition by spraying showed great technical potential in providing non-wood pellets from residual biomass from the separation/distillation of cellulosic bioethanol with mechanical attractiveness to power the strictest residential and industrial applications, even after freezing and defrosting. This alternative method enabled the normal, frozen, and defrosted pellets to be technically comparable to those from processing sugarcane bagasse [100][101][102], wheat straw [103], Moso bamboo [70], sewage sludge plus Chinese fir, camphor and rice straw [29], residues of olive tree [15], corn cob [104], and other woody and non-woody wastes [16,18,[105][106][107][108] that are often found in the production of fuel pellets (Table S7, Supplementary Material).…”
Section: Potential Applications For Non-wood Pellets From Residual Bi...mentioning
confidence: 99%